Collection Development in the Electronic Era - Wakhare, Abhijeet Sudhakar; Jaleel T., Abdul (DESIDOC Journal of Library & Information Technology, 2004)
An attempt has been made to discuss the collection development in the Internet era with the help of some of the sources available on the Internet in the area of pharmacology. It is argued that the Internet itself is a better tool for accessing the collection, rather than possessing it locally. A list of sources of information in the area of Pharmacology is also given. http://dx.doi.org/10.14429/dbit.17.1.8091